Airway Epithelial Cell Migration Dynamics: Mmp-9 Role in Cell–Extracellular Matrix Remodeling - Legrand, Claire (The Rockefeller University Press, 1999)
Cell spreading and migration associated with the expression of the 92-kD gelatinase (matrix metalloproteinase 9 or MMP-9) are important mechanisms involved in the repair of the respiratory epithelium. We investigated the location of MMP-9 and its potential role in migrating human bronchial epithelial cells (HBEC). In vivo and in vitro, MMP-9 accumulated in migrating HBEC located at the leading edge of a wound and MMP-9 expression paralleled cell migration speed. MMP-9 accumulated through an actin-dependent pathway in the advancing lamellipodia of migrating cells and was subsequently found active in the extracellular matrix (ECM). Lamellipodia became anchored through primordial contacts established with type IV collagen. MMP-9 became amassed behind collagen IV where there were fewer cell–ECM contacts. Both collagen IV and MMP-9 were involved in cell migration because when cell–collagen IV interaction was blocked, cells spread slightly but did not migrate; and when MMP-9 activation was prevented, cells remained fixed on primordial contacts and did not advance at all. These observations suggest that MMP-9 controls the migration of repairing HBEC by remodeling the provisional ECM implicated in primordial contacts.